PERAN WORLD HEALTH ORGANIZATION (WHO) DALAM MENANGANI PENYEBARAN WABAH VIRUS EBOLA DI AFRIKA BARAT TAHUN 2013-2014 - ", Hartarto; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes role of the World Health Organization in handle the spread of the Ebola outbreak in West Africa. World Health Organization has declared an emergency situation on the international health Ebola outbreak in West Africa, especially in Guneia, Lieberia and Sierra Leone which is a major threat to global security. World Health Organization has named the ebola virus as the virus must alert by the whole world. World Helath Organization asked all authorities to participate take the necessary action to prevent Ebola. World Health Organization wants a work programs and activities in the improvement of health services in countries affected Ebola is so far very bad. This study applies qualitative research method with library research. The data sources are from books, journals, and the internet. This study uses the role of international organizations theory and non-state level of analysis. The research shows that World Health Organization has an important role in handle with outbreaks Ebola in West Africa, especially in Gunie, Liberia and Sierra Leone. Through policy and strategy shape the draft strategy plan to eradicate outbreak of Ebola, the United Nations Mission for Ebola Emergency Response (UNMEER) to urgent international cooperation in eradicate Ebola in West Africa. World Health Organization urgen international cooperation to improve health faslities and treatment diseases in countries affected Ebola Key Words: World Health Organization, Strategi Shape, Foreign Policy